A novel CO2-tolerant Ba0.5Sr0.5Co0.8Fe0.1Ta0.1O3-δ cathode with high performance for proton-conducting solid oxide fuel cells. (28th September 2021) - Wang, Feihong; Xu, Xi; Xia, Yunpeng; Dong, Binbin; Ke, Nianwang; Hao, Luyuan; Bi, Lei; Xu, Xin; Liu, Wei
Abstract: The application of traditional MIEC cathode material Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) in the solid oxide fuel cell (SOFC) field is limited due to its susceptibility to CO2 and high thermal expansion coefficient. Therefore, improving the stability of BSCF cathode in CO2 -containing environments and the matching degree between BSCF and electrolyte are the key factors to achieve its excellent electrochemical and stable performance for intermediate temperature solid oxide fuel cells (IT-SOFCs). Herein, the cathode materials Ba0.5 Sr0.5 Co0.8 Fe0.2-x Tax O3-δ (X = 0, 0.1, 0.2) are successfully prepared and the effects of Ta-doped content are investigated systematically. With the increase of Ta-doped content, the thermal expansion coefficient of BSCF0.2-x Tx decreases from 25.1 × 10 −6  K −1 to 16.5 × 10 −6  K −1, which indicated that Ta-doped enhanced the combination of cathode material and electrolyte. In single-cell applications, the maximum power density of 926.4 mW cm −2 and the lowest polarization resistance of 0.06 Ω cm 2 at 700 °C are achieved. Furthermore, theoretical calculations show that the CO2 adsorption energy of BSCFT is 0.12 eV higher than that of BSCF, indicating that BSCFT exhibited improved resistance to CO2 corrosion compared with BSCF. It is indicated that the Ta-doping strategy has the advantage of improving both the performance and stability of BSCF cathode materials. Highlights: BSCF cathode materials doped with different concentrations of Ta were prepared. The good stability of Ta-doped BSCF cathode materials were confirmed. The effect of Ta doping on CO2 resistance was analyzed by theoretical calculations. BSCF0.1 T0.1 material achieved excellent fuel cell performance with good stability.